2004
DOI: 10.1111/j.1469-8749.2004.tb00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal representation of movement in children with developmental coordination disorder: a mental rotation task

Abstract: Recent studies show that children with developmental coordination disorder (DCD) have difficulties in generating an accurate visuospatial representation of an intended action, which are shown by deficits in motor imagery. This study sought to test this hypothesis further using a mental rotation paradigm. It was predicted that children with DCD would not conform to the typical pattern of responding when required to imagine movement of their limbs. Participants included 16 children with DCD and 18 control childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
104
3
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 35 publications
9
104
3
3
Order By: Relevance
“…DCD is not associated with any known neurological condition and its aetiology currently remains unexplained. However, a series of papers have provided evidence that suggests a deficit in the ability to utilise motor imagery effectively may underlie some of the motor impairment difficulties observed in children with this diagnosis (Deconinck, Spitaels, Fias, & Lenoir, 2009;Maruff, Wilson, Trebilcock, & Currie, 1999;Williams, Thomas, Maruff, Butson, & Wilson, 2006;Williams, Thomas, Maruff, & Wilson, 2008;Wilson et al, 2004;Wilson, Maruff, Ives, & Currie, 2001). Interestingly, a recent line of research has also begun examining whether motor imagery deficits may also be apparent in adolescents with hemiplegia, with these deficits adding to their already obvious motor execution difficulties (Mutsaarts, Steenbergen, & Bekkering, 2007;Steenbergen, van Nimwegen, & Crajé, 2007).…”
mentioning
confidence: 99%
“…DCD is not associated with any known neurological condition and its aetiology currently remains unexplained. However, a series of papers have provided evidence that suggests a deficit in the ability to utilise motor imagery effectively may underlie some of the motor impairment difficulties observed in children with this diagnosis (Deconinck, Spitaels, Fias, & Lenoir, 2009;Maruff, Wilson, Trebilcock, & Currie, 1999;Williams, Thomas, Maruff, Butson, & Wilson, 2006;Williams, Thomas, Maruff, & Wilson, 2008;Wilson et al, 2004;Wilson, Maruff, Ives, & Currie, 2001). Interestingly, a recent line of research has also begun examining whether motor imagery deficits may also be apparent in adolescents with hemiplegia, with these deficits adding to their already obvious motor execution difficulties (Mutsaarts, Steenbergen, & Bekkering, 2007;Steenbergen, van Nimwegen, & Crajé, 2007).…”
mentioning
confidence: 99%
“…Together, these findings illustrate that unpredictability of the required motor response crucially underpins poorer visuomotor performance of very preterm children compared with those born at term, regardless of motor abilities and DCD status. Given our findings that visuomotor problems are particularly present in unpredictable, non-structured circumstances, insensitive to an increase in workload, we speculate that an inability to generate accurately and use internal models of motor planning and continuous motor control, as described for children with DCD, 10 also plays a crucial role in the visuomotor problems of very preterm children with and without a research diagnosis of DCD. Importantly, these findings suggest that visuomotor performance of very preterm children free of motor impairment may potentially benefit from the same interventions as those developed for children with DCD, 22 given that similar underpinnings of visuomotor deficits appear to be present for both groups.…”
Section: Discussionmentioning
confidence: 99%
“…By having internal models or representations of intended actions, predicting the outcome of movements can be processed much quicker in the brain than when a person has to rely on relatively slow sensory-feedback information, thereby providing efficiency to the brain's motor system. 8 Recent studies suggest that visuomotor problems in children with developmental coordination disorder (DCD) are related to specific 'internal modelling deficits', 9,10 which limit their ability to generate accurately and use internal models of motor planning and continuous motor control. Interestingly, the incidence of DCD in very preterm children is on average more than six times higher than in term peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, later studies have shown that, at least in participants with motoric deficits, different strategies might also be used when body part stimuli are rotated (Steenbergen, Nimwegen, & van Craje, 2007;Tomasino & Rumiati, 2004;Wilson et al, 2004). Wilson et al, for example, observed that children with a developmental coordination disorder displayed an RT pattern for right-/lefthand decisions that was more consistent with an object-based than with a motor imagery strategy.…”
Section: Abstract Embodied Cognition Social Cognition Mental Modelsmentioning
confidence: 99%